Structure and thermomechanical properties of stretched cellulose films. Issue 1 (25th June 2012) - Kim, Jae‐Woo; Park, Sunkyu; Harper, David P.; Rials, Timothy G.
Abstract Regenerated and stretched cellulose films were investigated for structure and thermomechanical properties as a potential packaging material. Cellulose films were cast from lithium chloride/N, N‐dimethylacetamide and were stretched up to 30% in a dynamic mechanical analyzer sample holder. Wide‐angle X‐ray diffraction analysis indicated that the orientation factor was significantly increased due to stretching. In addition, the stretched films have a higher resistance to the thermal decomposition from thermo gravimetric analysis. The increased orientation of cellulose crystalline structure by the stretching process also increased the storage modulus of cellulose films characterized by dynamic mechanical analysis, which suggest that mechanical properties of cellulose films could be tuned during the stretching process. The α2 and α1 relaxations were found at 240 and 300°C, respectively, which are attributed to the micro‐Brownian motion of segments in amorphous region, and activation energies for relaxations were determined with the stretching levels. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013